(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
According to Rosstat data for 2002-2023 on the dynamics of gross output, value added, fixed assets, number and salary for financial activities of the Russian Federation, forecasts were made for 3 types of regression (autoregression, reflexive regression, multiple reflexive regression). As a result, the most plausible forecast scenarios up to 2028 were obtained, which allowed us to draw a general conclusion about the prospects for development.